The effects of yawn-sigh, lip trill and tongue relaxation exercises on frequency and amplitude perturbation of voice in vocal training - MALKOÇ, TÜLÜN (My University, 2022)
In this study, the usability of lip trill, yawn–sigh and tongue relaxation exercises in vocal training programmes was evaluated. The exercise programmes were carried out with first-year students in a music teacher education programme, and the effect of these exercises on the quality of the voice was measured using acoustic measurement techniques. Thirty-one subjects were included in the study. The experimental group (n = 16) and the control group (n = 15) were determined randomly. While determining the groups, attention was paid to ensure that the characteristics of the groups were the same. An 8-week vocal exercise programme (one session per week) was carried out with the students in the experimental group. The voices of the students were recorded before and after each exercise, and then acoustic measurements of these recordings were made. The data obtained from the measurements conducted before the vocal exercises were compared with the measurement data obtained after the vocal exercises were carried out. The significance assessment of the differentiation of voice parameters in both the short term (comparison of the data obtained before the exercise and the data obtained immediately after the exercise) and in the long term (after the 8-week implementation phase) was made. A significant improvement was shown in voice quality in terms of frequency and amplitude perturbation parameters compared to the control group after each session and at the end of the 8-week exercise programme.
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Sanat Eğitimi; Müzik Eğitimi; Social Sciences and Humanities; Education; Education in Art; Education in Music; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; EĞİTİM, BİLİMSEL DİSİPLİNLER; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; EDUCATION, SCIENTIFIC DISCIPLINES; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Vocal training; music education; lip trill; yawn-sigh; tongue relaxation; frequency perturbation; amplitude perturbation